DM-Tune: Quantizing Diffusion Models with Mixture-of-Gaussian Guided Noise Tuning - Haghi, Pouya; Falahati, Ali; Azad, Zahra; Wu, Chunshu; Song, Ruibing; Liu, Chuan; Li, Ang; Geng, Tong (2025 62nd ACM/IEEE Design Automation Conference (DAC), 2025)
Diffusion models have become essential generative tools for tasks such as image generation, video creation, and inpainting, but their high computational and memory demands pose challenges for efficient deployment. Contrary to the traditional belief that full-precision computation ensures optimal image quality, we demonstrate that a fine-grained mixed-precision strategy can surpass full-precision models in terms of image quality, diversity, and text-to-image alignment. However, directly implementing such strategies can lead to increased complexity and reduced runtime performance due to the overheads of managing multiple precision formats and casting operations. To address this, we introduce DM-Tune, which replaces complex mixed-precision quantization with a unified low-precision format, supplemented by noise-tuning, to improve both image generation quality and runtime efficiency. The proposed noise-tuning mechanism is a type of fine-tuning that reconstructs the mixed-precision output by learning adjustable noise through a parameterized nonlinear function consisting of Gaussian and linear components. Key steps in our framework include identifying sensitive layers for quantization, modeling quantization noise, and optimizing runtime with custom low-precision GPU kernels that support efficient noise-tuning. Experimental results across various diffusion models and datasets demonstrate that DM-Tune not only significantly improves runtime but also enhances diversity, quality, and text-to-image alignment compared to FP32, FP8, and state-of-the-art mixed-precision methods. Our approach is broadly applicable and lays a solid foundation for simplifying complex mixed-precision strategies at minimal cost.